2017
DOI: 10.37855/jah.2017.v19i03.39
|View full text |Cite
|
Sign up to set email alerts
|

Studies on in vitro antiproliferative activities in Cruciferae vegetables

Abstract: Cruciferous vegetables have drawn a great deal of attention in cancer research because of their potential protective properties. In the present study, four vegetables viz. cabbage, cauliflower, kohlrabi and radish were procured and processed for cold extraction procedure using 70% ethanol. The extracts were subjected to the qualitative phytochemical analysis, quantitative estimation of glucosinolates content and in vitro antiproliferative activity by MTT assay on MCF7, DL and NIH-3T3 cell lines. The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…As shown in Figure 3 a, there was a concentration-dependent inhibition of MCF-7 proliferation for RAE and RPI at all hydrolysis degrees. Other studies with DRM are consistent with this result [ 5 , 17 , 33 , 34 ]. The results showed that RAE (C, DH0, DH2) and RPI (C, DH0, DH1) each had an inhibition equal to and greater than 80% of the MCF-7 proliferation at a 10 mg/mL concentration.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…As shown in Figure 3 a, there was a concentration-dependent inhibition of MCF-7 proliferation for RAE and RPI at all hydrolysis degrees. Other studies with DRM are consistent with this result [ 5 , 17 , 33 , 34 ]. The results showed that RAE (C, DH0, DH2) and RPI (C, DH0, DH1) each had an inhibition equal to and greater than 80% of the MCF-7 proliferation at a 10 mg/mL concentration.…”
Section: Resultssupporting
confidence: 87%
“…However, for RPI, the inhibition of cell proliferation among the C, DHO, DH1 and DH2 extracts was comparable at 7.5 and 10 mg/mL. Similar results were presented by Jamuna et al (2017) [ 33 ], who demonstrated that the difference in the inhibitory effects of SKOV3 cancer cell proliferation between a soy protein (69%) and its hydrolysates (64%) was not significant. However, in this work the proteolytic hydrolysis with Alkalase 2.4 L FG improves the antiproliferative effect on the MCF-7 of RPI DH1 and DH2 at low concentrations.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…There are previous studies confirm our results and the cytotoxic effect of Brassica vegetable extracts against the proliferation of cancer cell lines. Four cruciferous vegetables cabbage, cauliflower, kohlrabi, and radish showed antiproliferative activity expressed as IC50 against three cell lines (MCF7, DL, and NIH-3T3), cabbage (92.5, 189.7, 589.7 μg/ml) followed by cauliflower (378.7, 398.9, 597.9 μg/ml), kohlrabi (389.5, 396.9, 619.7 μg/ml) and radish (415.4, 423.3, 703.6 μg/ml), respectively by MTT assay (48). Furthermore, the water extract of green and red cabbage exhibited the cytotoxic effect (as IC 50 ) on MCF 7 cell lines 176, 40 μg/ml, and 1125, 342 μg/ml at 24 and 48 h, respectively by using Alamar Blue Assay (49).…”
Section: Biological Studies Cytotoxic Effectsmentioning
confidence: 99%
“…Leafy vegetables are not only the essential sources of natural antioxidants, such as various pigments and phenolic compounds, but also the key sources of minerals, proteins, dietary fiber, and vitamins for human nutrition, in which the bioactive metabolites such as carotenoids, phenolic acids, flavonoids, vitamin A, tocopherols, and phylloquinone, as well as glucosinolates (GLS, also a category of bioactive metabolites uniquely found in Cruciferous crops for defending plants from virus and pest attacks), greatly contribute to the nutritional value of vegetables. These compounds have significant roles in antioxidant, anticancer, antiproliferative, and anti-inflammatory activities on human health and have garnered extensive attention in recent years. The biosynthesis of some of the above metabolites in vegetables has been proven to be sensitive to various properties of light, especially light intensity. Therefore, many studies have focused on this field recently, targeting the enhancement of their levels by means of photoinduction, which is a simple and efficient approach for improving the nutritional quality of vegetables. …”
Section: Introductionmentioning
confidence: 99%